Na+/H+ exchange is inactivated during mouse oocyte meiosis, facilitating glycine accumulation that maintains embryo cell volume. Issue 10 (20th June 2013) - Zhou, Chenxi; Fitzharris, Greg; Alper, Seth L.; Baltz, Jay M.
Abstract The coupled action of the Na+/H+ exchanger NHE1 and the HCO3−/Cl− exchanger AE2 constitutes the principal mechanism for acute correction of decreased cell volume in mammalian somatic cells, while, when acting separately, they regulate intracellular pH. It was previously found that AE2 becomes inactivated during meiosis in mouse oocytes. Similarly, NHE1 activity stimulated by intracellular acidosis was present in preovulatory germinal vesicle stage (GV) mouse oocytes and then decreased during meiotic maturation. In contrast, NHE1 activity stimulated by decreased cell volume was low in GV oocytes but became active during meiotic maturation as the oocyte detached from the zona pellucida. It then decreased again in mature eggs similar to activity stimulated by acidosis. The subcellular localization of NHE1 was investigated with YFP‐tagged NHE1. Exogenous NHE1 expressed in GV oocytes localized to the plasma membrane and resulted in increased Na+/H+ exchanger activity, but only when co‐expressed with calcineurin homologous protein 1 (CHP1). When oocytes expressing functional NHE1 were matured to eggs, however, membrane localization of NHE1 and Na+/H+ exchanger activity were lost. It was unknown why NHE1 and AE2 activities are suppressed during meiotic maturation. Maintenance of cell volume in preimplantation embryos requires glycine accumulation via the GLYT1 transporter, a process unique to eggs and early embryos that is initiated during meiotic maturation. When NHE1 and AE2 activities were maintained in GV oocytes by exogenous expression, glycine accumulation was inhibited. We propose that NHE1‐mediated acute cell volume regulation is inactivated during meiotic maturation to allow preferential accumulation of glycine in eggs. J. Cell. Physiol. 228: 2042–2053, 2013. © 2013 Wiley Periodicals, Inc.